2022
DOI: 10.1038/s41467-022-34633-7
|View full text |Cite
|
Sign up to set email alerts
|

A fourth dose of the inactivated SARS-CoV-2 vaccine redistributes humoral immunity to the N-terminal domain

Abstract: The effectiveness of a 3rd dose of SARS-CoV-2 vaccines waned quickly in the Omicron-predominant period. In response to fast-waning immunity and the threat of Omicron variant of concern (VOC) to healthcare workers (HCWs), we conduct a non-randomized trial (ChiCTR2200055564) in which 38 HCWs volunteer to receive a homologous booster of inactivated vaccines (BBIBP-CorV) 6 months after the 3rd dose. The primary and secondary outcomes are neutralizing antibodies (NAbs) and the receptor-binding domain (RBD)-directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…By studying the antigenspecificity of the Spike response, we identified Spike/NTD as a specific IgA target that correlated with seroneutralization titers. A shift of the humoral response toward the Spike/NTD domain had previously been described after the second boost, despite the fact that some Omicron sublineages displayed several NTD mutations (38). Monoclonal antibodies targeting the Spike/NTD have shown in previous studies their ability to inhibit cell-to-cell fusion, to activate effector functions and to protect Syrian hamsters from SARS-CoV-2 challenge (39).…”
Section: Discussionmentioning
confidence: 90%
“…By studying the antigenspecificity of the Spike response, we identified Spike/NTD as a specific IgA target that correlated with seroneutralization titers. A shift of the humoral response toward the Spike/NTD domain had previously been described after the second boost, despite the fact that some Omicron sublineages displayed several NTD mutations (38). Monoclonal antibodies targeting the Spike/NTD have shown in previous studies their ability to inhibit cell-to-cell fusion, to activate effector functions and to protect Syrian hamsters from SARS-CoV-2 challenge (39).…”
Section: Discussionmentioning
confidence: 90%
“…By studying the antigenspecificity of the Spike response, we identified Spike/NTD as a specific IgA target that correlated with seroneutralization titers. A shift of the humoral response toward the Spike/NTD domain had previously been described after the second boost, despite the fact that some Omicron sublineages displayed several NTD mutations (37). Monoclonal antibodies targeting the Spike/NTD have shown in previous studies their ability to inhibit cell-to-cell fusion, to activate effector functions and to protect Syrian hamsters from SARS-CoV-2 challenge (38).…”
Section: Discussionmentioning
confidence: 90%
“…Wang et al demonstrated that non-spike and spike T cell responses as assayed by ELISPOT were readily detectable 6 months after the third dose of inactivated vaccine BBIBP-CorV (Covilo). A homologous booster 6 months after the third dose failed to further enhance T cell responses (39). Melo-Gonzaĺez et al reported that AIM + CD4 + T cell response remained stable after the third dose of CoronaVac, but showed a decline 4-6 months later (40).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that non-spike and spike T cell responses as assayed by ELISPOT were readily detectable 6 months after the third dose of inactivated vaccine BBIBP-CorV (Covilo). A homologous booster 6 months after the third dose failed to further enhance T cell responses ( 39 ). Melo-González et al.…”
Section: Discussionmentioning
confidence: 99%